Three-dimensional atomic scale electron density reconstruction of octahedral tilt epitaxy in functional perovskites. Issue 1 (December 2018) - Yuan, Yakun; Lu, Yanfu; Stone, Greg; Wang, Ke; Brooks, Charles; Schlom, Darrell; Sinnott, Susan; Zhou, Hua; Gopalan, Venkatraman
Abstract Octahedral tilts are the most ubiquitous distortions in perovskite-related structures that can dramatically influence ferroelectric, magnetic, and electronic properties; yet the paradigm of tilt epitaxy in thin films is barely explored. Non-destructively characterizing such epitaxy in three-dimensions for low symmetry complex tilt systems composed of light anions is a formidable challenge. Here we demonstrate that the interfacial tilt epitaxy can transform ultrathin calcium titanate, a non-polar earth-abundant mineral, into high-temperature polar oxides that last above 900 K. The comprehensive picture of octahedral tilts and polar distortions is revealed by reconstructing the three-dimensional electron density maps across film-substrate interfaces with atomic resolution using coherent Bragg rod analysis. The results are complemented with aberration-corrected transmission electron microscopy, film superstructure reflections, and are in excellent agreement with density functional theory. The study could serve as a broader template for non-destructive, three-dimensional atomic resolution probing of complex low symmetry functional interfaces. In complex oxides, oxygen octahedra are major structural motifs and their tilts sensitively determine the material's physical properties. Exploiting Coherent Bragg Rod Analysis enables 3D mapping of complex tilt patterns and reveals the means to control polarization through them in CaTiO3 thin films.